2015
DOI: 10.1016/j.ijsu.2015.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the universal adoption of bilateral internal mammary artery grafting

Abstract: The left internal mammary artery (LIMA) graft is considered the "gold standard" of coronary artery bypass grafting (CABG). This conduit provides increased survival, symptomatic relief, increased freedom from myocardial infarction, and increased freedom from re-intervention when compared to saphenous venous grafting. It has a remarkable long term patency rate with clinical and angiographic outcomes that are unmatched by other conduits. Given the fact that patients often require more than one graft during a coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Kamiya et al [28] showed that the oxygen saturation and blood flow in the microcirculation of the sternum tissue were better when using the skeletonized ITA compared to pedicled ITA. Despite the beneficial impact of skeletonization on reducing the risk of sternal wound infection it is important to emphasize that skeletonization is technically more demanding and more time-consuming than pedicled ITA harvesting with a steep learning curve associated with it [29-31] . Furthermore, some surgeons have raised concerns about the quality of the graft, mainly when it comes to the patency and the flow capacity of the skeletonized ITA.…”
Section: Discussionmentioning
confidence: 99%
“…Kamiya et al [28] showed that the oxygen saturation and blood flow in the microcirculation of the sternum tissue were better when using the skeletonized ITA compared to pedicled ITA. Despite the beneficial impact of skeletonization on reducing the risk of sternal wound infection it is important to emphasize that skeletonization is technically more demanding and more time-consuming than pedicled ITA harvesting with a steep learning curve associated with it [29-31] . Furthermore, some surgeons have raised concerns about the quality of the graft, mainly when it comes to the patency and the flow capacity of the skeletonized ITA.…”
Section: Discussionmentioning
confidence: 99%
“…2-7 In addition, the advantage of skeletonized internal mammary artery grafting is that it serves to minimize chest wall trauma, achieves maximal length, and facilitates the ease of sequential grafting. 8 Sequential grafting of the in situ skeletonized LIMA to the left coronary system (to the diagonal artery and then to the LAD) is a common strategy of sequential Sequential vs. Separate LIMA Grafting from this study on the basis of the following criteria: patients with any concomitant diseases including renal insufficiency (preoperative creatinine >2 mg/dL or need of renal replacement therapy), 10 malignant tumor, and chronic obstructive pulmonary disease; and patients undergoing in situ skeletonized LIMA grafting to the left coronary system other than the LAD.…”
Section: Lima Graftingmentioning
confidence: 99%
“…6) Given the fact that patients who received CABG surgery often require more than one graft, the prospect of bilateral IMA grafting becomes very appealing to cardiac surgeons after recognition of the long-term benefits of left IMA graft. 7) However, the use of bilateral IMA grafting is scarcely diffused. 8,9) Concerns regarding a higher probability of deep sternal wound infections and its ensuing complications, an increased operation time, and technical challenges including utilizing and teaching the technique, have limited the widespread use of bilateral IMA grafting.…”
mentioning
confidence: 99%
“…7) A skeletonized IMA graft compared to a pedicled IMA graft preserves collateral circulation to the sternum and drainage of the internal mammary veins, and has been shown to reduce the risk of Ji sternal wound infection while maintaining the benefits of the application of IMA graft. 12,13) Additionally, a recently published propensity score adjusted analysis investigated the impacts of the in situ right IMA grafting to the LAD on the long-term mortality and the need for repeat revascularization, and validated the safety and efficacy of the in situ right IMA grafting to the LAD.…”
mentioning
confidence: 99%